On the Influence of Modulus of Subgrade Reaction and the Wavelength of Corrugation on Bifurcation of Thin Corrugated Shell Lying on Elastic Foundation under Action of Hydrostatic Pressure - S.P. Kuntsevich (Механика машин, механизмов и материалов, 2009)
The problem of buckling of a thin corrugated shell lying on elastic foundation under action of the non-uniform hydrostatic pressure is considered. The influence of the elastic foundation is taken into account as the additional pressure within the framework of Winkler`s model. The semi-moment equations of the thin elastic shell theory are assumed as the governing ones. The rigid clamped conditions are considered at the edges of the shell. Assuming that the hydrostatic pressure depends upon the circumferential co-ordinate, solutions of the governing equations are constructed in the form of functions decaying far from some generator on the shell surface. Using the complex WKB-method, the boundary-value problem is reduced to the sequence of the one-dimensional boundary-value problems. Its numeric solution has been obtained. The influence of parameters of corrugation of the shell and modulus of subgrade reaction on the critical pressure has been analyzed.